Sevoflurane increases intracellular calcium to induce mitochondrial injury and neuroapoptosis. (1st January 2021) - Zhu, Xiaoqiu; Yao, Yiyi; Guo, Mingyan; Li, Jin; Yang, Pengfeng; Xu, Hui; Lin, Daowei
Graphical abstract: Highlights: Sevoflurane (Sevo) increases intracellular Ca 2+ concentration in neurons. Sevo-induced increment of intracellular Ca 2+ induces mitochondrial injury. Sevo-induced increment of intracellular Ca 2+ causes neuroapoptosis. The Sevo-induced increment of intracellular Ca 2+ may be via L-type Ca 2+ channel. Abstract: Sevoflurane is commonly used in clinical anesthesia. However, some reports indicated that Sevoflurane could induce mitochondrial injury and neuroapoptosis. Although the mechanism remains unclear, evidence points to the increase of intracellular calcium after administration of Sevoflurane. Herein, we sought whether the increment of intracellular Ca 2+ caused by Sevoflurane administration could induce mitochondrial injury and apoptosis in primary neurons of the hippocampus. Fluo-4-acetoxymethyl ester Ca 2+ probe was used for measuring intracellular Ca 2+ concentrations. LDH assay, CCK-8 assay, and Western blotting were performed to confirm Sevoflurane-induced neuroapoptosis. ROS, mPTP, and ATP production were assayed to reveal mitochondrial injury. Our results indicated that Sevoflurane increased intracellular Ca 2+ and neuronal death. Sevoflurane also elevated ROS and the opening of mPTP, and decreased ATP production in neurons. The expression of cytochrome c, cleaved caspase-9, cleaved caspase-3, and the ratio of Bax/Bcl-2 were also increased. By using calcium channel blocker Nimodipine, the increase of intracellular Ca 2+ was attenuated, and the death rate of neurons, the ROS and opening of mPTP, decreased ATP production, the expressions of cytochrome c, cleaved caspase-9, cleaved caspase-3 and the ratio of Bax/Bcl-2 were alleviated. Our study suggested that Sevoflurane could increase intracellular Ca 2+ to induce mitochondrial injury and mitochondria-mediated neuroapoptosis in neurons.